ANALYSIS OF TECHNOLOGICAL INDICATORS OF KNITTED FABRICS - Saparova Sarvinoz Akram qizi; Musayeva Muhayyo Mirxatamovna; Mirsadikov Mirzait Mirzaxidovich; Mukimov Mirabzal Mirayubovich (Journals Park Publishing, 2025)
The article presents the results of studying the technological parameters of knitted fabrics made from PAN yarn. Parameters such as loop pitch, loop row height, horizontal and vertical density, surface and volumetric density, yarn length in the loop, and knitted fabric thickness were analyzed.
Keywords: knitwear, PAN yarn, assortment, quality, loop pitch, horizontal density, vertical density, surface density, volumetric density.